Dinámica familiar y desempeño académico de estudiantes de séptimo grado de la escuela de educación básica “Vicente Bastidas Reinoso” de la ciudad de Loja, periodo 2021/2022 - Riofrio Vega, Nayeli Lizbeth (2022)
This research work entitled “Family dynamics and academic performance of seventh- grade students from the "Vicente Bastidas Reinoso” Basic Education School in the city of Loja, 2021-2022 academic year” had as general objective to analyze the influence of family dynamics on the academic performance of the seventh-grade students from the Vicente Bastidas Reinoso Basic Education School during the 2021-2022 academic year. It was developed under a quantitative approach, descriptive type, non-experimental, and cross-sectional design. The methods employed were: scientific, deductive-inductive, as well as analytical-synthetic. To fullfill the objective, the instruments administered were the family dynamics measurement scale of Valdés Cuervo, Ángel (2011) adaptation: Cahuas and Gonzales (2021) and the self- perception of school performance questionnaire of Guachamín and Luna (2019). The results gathered showed that within the characteristics of family dynamics in the investigated population, communication is 70% at a moderate level; the authority in 61% at the moderate level whereas the parenting guidelines are 78% at a moderate level. In relation to affectivity, 83% are at a low level. Lastly, with respect to the academic performance of the students, 43% of the population has a low level. It is concluded that family dynamics present moderate levels of communication, authority, parenting patterns and low levels of affectivity, which influence students not to achieve a high level of academic performance. Keywords: Family dynamics, academic performance, family support, family roles, parenting guidelines.